Dickkopf proteins in pathological inflammatory diseases. Issue 4 (10th December 2021) - Park, Min Hee; Shin, Jae Hun; Bothwell, Alfred L M; Chae, Wook-Jin
Abstract: The human body encounters various challenges. Tissue repair and regeneration processes are augmented after tissue injury to reinstate tissue homeostasis. The Wnt pathway plays a crucial role in tissue repair since it induces target genes required for cell proliferation and differentiation. Since tissue injury causes inflammatory immune responses, it has become increasingly clear that the Wnt ligands can function as immunomodulators while critical for tissue homeostasis. The Wnt pathway and Wnt ligands have been studied extensively in cancer biology and developmental biology. While the Wnt ligands are being studied actively, how the Wnt antagonists and their regulatory mechanisms can modulate immune responses during chronic pathological inflammation remain elusive. This review summarizes DKK family proteins as immunomodulators, aiming to provide an overarching picture for tissue injury and repair. To this end, we first review the Wnt pathway components and DKK family proteins. Next, we will review DKK family proteins (DKK1, 2, and 3) as a new class of immunomodulatory protein in cancer and other chronic inflammatory diseases. Taken together, DKK family proteins and their immunomodulatory functions in chronic inflammatory disorders provide novel insights to understand immune diseases and make them attractive molecular targets for therapeutic intervention. Graphical Abstract: Review on Dickkopf family proteins as immunomodulatory ligands in cancer and other inflammatory diseases.